Analysis of size effects on thermoelastic damping in the Kirchhoff's plate resonator under Moore–Gibson–Thompson thermoelasticity - Singh B.; Kumar H.; Mukhopadhyay S. (My University, 2025)
Nanoresonators with ultra-high resonant frequency have found useful applications as electromechanical systems in today's time. This current work presents an analytical technique for measuring thermoelastic damping (TED) and dynamic behavior of micro/nano Kirchhoff plate resonators using Moore–Gibson–Thompson (MGT) generalized thermoelasticity theory. Modified couple stress theory (MCST) is employed here to take into account the size effect for micro/nano plate. This work comprehensively evaluated the frequency shift and normalized attenuation in the micro plate resonator in the frame of the recently introduced MGT thermoelasticity theory to obtain the closed-form analytical expression for quality factor (QF). The outcomes are compared with the corresponding results of classical continuum theory and classical thermoelasticity theory. Finally, the influence of various parameters including size effects on TED in micro plate resonators has been investigated by carrying out the numerical computation of the present analytical results for different materials. Several important points are highlighted. © 2022 Elsevier Ltd